STUDY ON SERVICE QUALITY OF TELKOMSEL MANADO BY USING IMPORTANCE AND PERFORMANCE ANALYSIS - Masengi, Eunike I. (Sam Ratulangi University, 2016)
In today's conditions of the times and technological advances increasingly sophisticated, and societal needs from time to time more complex. To facilitate human activities necessary tool communications include information technology. One of the business sector in the service industry in Indonesia is experiencing rapid growth is the telecommunications industry. This makes competition in telecommunications is getting stronger. This competition involves many things, not only in the form of products, product quality, product prices, but also in terms of services provided. Telkomsel as one of the largest telecommunications company in Indonesia, to be able to maintain a presence and to remain in demand by customers must create a long-term marketing strategy, among others through service to our loyal customers, especially a quality service or quality of service. The purpose of this research is to examine how is the important of service quality in Telkomsel Manado, and how is the performance of service quality in Telkomsel Manado by applying Importance and Performance Analysis method.Â The result of the analysis is the mean values of the attributes in Importance are higher than mean values in Performance this means the respondents perceived of Telkomsel in Manado is highly important while the performance is less than what expected. The researcher hoped that the findings may assist the mobile phone operators to improve their performance make customers satisfied and loyal in order to achieved the companyâ€™s goals.